TRADISI POAGO DAN KAOMBO PADA MASYARAKAT MBANUA KECAMATAN SIOMPU BARAT KABUPATEN BUTON SELATAN - saafi, nasrun (Jurnal Pendidikan Sejarah, 2023)
This study examines and reveals the Poago and Kaombo Traditions in the Mbanua Community, West Siompu District, South Buton Regency, to find out the background of the Poago traditional medicine tradition and the Kaombo prohibition protection tradition and to know the practices and procedures for implementing the Poago tradition and the Kaombo tradition. This type of study was qualitative research. Data collection was carried out in Mbanua Village, West Siompu District, South Buton Regency by relying on interviews, observation, and literature study approaches. The results showed that the background of the poago traditional medicine tradition was the concern and fear of the community for something that would happen to their lives at the turn of the season commonly known as the term kalelei. The background of the tradition of protection and prohibition of kaombo was to maintain, protect, and preserve the protected forest as well as to maintain and protect garden products and fruit plants. The process of implementing the poago traditional medicine tradition was carried out in the mosque and led by an Islamic religious leader (Imam) by reading and reciting tobah astaghfirullah (100 times), shalawat on the prophet (100 times), Allahumma ya mahmudu (200 times), Al-Ikhlas (100 times), and rahatibu laailaahaillallah (100 times). The implementation of the tradition of protection and prohibition of kaombo was led by parabela traditional leaders starting with preparing the completeness of the procession, wrapping the completeness of the materials that had been prepared with white cloth then tied and hung on bamboo sticks, then stored in a place or tree that would be kaombo accompanied by reading batata (prayers).